Studi Kelayakan Finansial Pembangunan Proyek Pasar (Studi Kasus : Pasar Induk Kota Pekanbaru) - Novelia Miranda Hilman; Rian Trikomara Irana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The city of Pekanbaru is known as an investment destination city. Therefore it is necessary facilities and infrastructure that can support the progress of the city, especially in the field of economy one of them with the development of Pasar Induk Pekanbaru. The development of Pasar Induk Pekanbaru using the system Build Operate Transfer (BOT) where the project is planned for 30 years of operation and after the completion of the operation will be submitted to the city government of Pekanbaru. Project development requires large capital so that research and financing analysis and project funding needs to be done. So the purpose of this study is to analyze the feasibility of financial aspects and to know the occupancy of building units. The investment criteria used are Net Present Value, Benefit Cost Ratio, Internal Rate of Return, Payback Period and also Sensitivity Analysis. The results show that the total market investment amounts to "Rp.111.146.973.858,46". NPV of Rp. 19.660.493.750,74 ", BCR of 1.08, IRR of 15.74% and PP for 15 years 8 months. Overall, the investment project for the construction of Pasar Induk Pekanbaru is feasible to build with aoccupancy of 44.23%. The sensitivity analysis indicates that parameter changes of 10% magnitude can give a significant influence on the feasibility analysis result.Keywords: Financial Analysis, Sensitivity Analysis, Pasar Induk Pekanbaru, The occupansy of building units.